2012
DOI: 10.1111/j.1468-2273.2012.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Research Capacity at United States Universities: a Study of Academic Research and Development Investment from 1990–2005

Abstract: Growing emphasis has been placed on universities to contribute to the innovation process and as a result academic research and development expenditures have increased in recent years. Nevertheless, little is known about the specific ways in which universities have expanded their research capacity. This paper examines how universities in the United States (US) have expanded research capacity as research funding has increased. Specifically, it identifies what type of research infrastructure, including various ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The AAU is the oldest and arguably the most elite association of research universities in North America and having membership has shown to be a decidedly positive predictor of an institutions’ research capacity (Cantwell and Mathies, 2012). It develops national policy positions on issues related to academic research and graduate and professional education and provides a forum for discussing a broad range of other institutional issues.…”
Section: Introductionmentioning
confidence: 99%
“…The AAU is the oldest and arguably the most elite association of research universities in North America and having membership has shown to be a decidedly positive predictor of an institutions’ research capacity (Cantwell and Mathies, 2012). It develops national policy positions on issues related to academic research and graduate and professional education and provides a forum for discussing a broad range of other institutional issues.…”
Section: Introductionmentioning
confidence: 99%
“…State-led postsecondary systems are consistently more likely to propel R&D capacity including in the private R&D sector. Within this group of strong state-backed systems, we find such diverse cases as Singapore, South Korea and Denmark which all prove that strong state oversight does not contradict the dynamic of R&D expansion (Cantwell and Mathies 2012 ; Etzkowitz and Leydesdorff 2000 ; Mok 2010 ). This finding is also in line with previous research which sees the state as an active agent in “interventionist” research governance (Zapp, Helgetun and Powell 2018 ; Elzinga 2012 ; Cozzens and Woodhouse 1995 ).…”
Section: Discussion: Bringing the State Back Into The Schooled Society?mentioning
confidence: 64%
“…Related arguments hold that R&D expansion is a function of investments into knowledge infrastructure. For academic R&D expansion, this line of explanation echoes so-called "externalist" arguments from the sociology of science whereby the growth of science is primarily determined by conditions outside of academia, notably funding (Cantwell and Mathies 2012;Elzinga 2012). Following this logic, richer countries dedicate more resources to their training and research systems, and can accommodate larger numbers of researchers who in turn, enter industry and transform jobs and labor markets.…”
Section: Economic Arguments: Development and Investmentsmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been challenging for the social work profession (among others) to develop academic cultures to enhance their research capacity (Barner, Holosko, Thyer, & King, 2015; Cantwell & Mathies, 2012; Holosko & Barner, 2014; McRoy, Flanzer, & Zlotnik, 2012). These difficulties in the United States have led to (a) the widening of the long-standing schism between social work researchers and practitioners, (b) the profession’s proclivity to appending research to practice rather indiscriminately rather than using an integrative evidence-informed approach, (c) precluding the conduct of research and evaluation in local agencies and organizations where social work is practiced, and (d) minimizing the importance of research to the profession overall (Barner et al, 2013).…”
mentioning
confidence: 99%